The proAKAP4 concentrations in Nelore bull sperm and their relation to FTAI conception rate results - de Almeida, Ana Beatriz Marques; Hidalgo, Myrian Megumy Tsunokawa; de Moraes, Fábio Lucas Zito; Trautwein, Luiz Guilherme Corsi; de Fátima Schnitzer, Josiana; Silva, Letícia Amanda dos Santos; Rizzoto, Guilherme [UNESP]; Ferreira, João Carlos Pinheiro [UNESP]; Martins, Maria Isabel Mello (Elsevier, 2022)
The AKAP4 protein has an essential role in sperm motility, and its precursor, the proAKAP4, is considered a biomarker for sperm quality and fertility. Despite this, proAKAP4 concentration was never evaluated in Bos indicus sperm. Therefore, this study aims to determine the proAKAP4 concentration in the sperm of Nellore bulls and its association with sperm kinetics, morpho-functionality, morphology, and conception rates after fixed-time artificial insemination (FTAI). The bulls (n = 9) used in our study presented sperm characteristics above expected standards for quality. Sperm from each bull was evaluated regarding kinetics by the CASA system, and assessed for mitochondrial functionality, sperm membrane integrity, and morphology. For the FTAI protocol, multiparous Nelore cows (n = 1507) were inseminated with frozen-thawed sperm from the same batches used in the laboratory analysis. Additionally, the sperm proAKAP4 concentration was determined using an ELISA kit. The data were analyzed by linear regression and the significance level was set to 5%. The mean conception rate was 52.52%. The mean proAKAP4 concentration was 25.75 ng/106 spermatozoa. The proAKAP4 concentration positively affected the sperm total and progressive motilities, and conception rates after FTAI (respectively, r2 = 0.49, P = 0.03; r2 = 0.63, P = 0.01; and r2 = 0.51, P = 0.03). Based on the relationship detected in this study, we conclude that the sperm proAKAP4 concentration is a suitable biomarker to predict the quality and fertility of frozen-thawed Bos indicus semen.
Keywords: AKAP4 protein; Artificial insemination; Biomarker; Fertility; Nelore bulls